Қ.Өмірəлиев жəне қазақ филологиясы - Жұмағұлов, С.Б. (ҚарМУ баспасы, 2011)
Автором анализируются особенности и актуальность филологических трудов К.Омиралиева. Показано комплексное изучение ученым исторических связей казахской и древнетюркской литературы в аспектах генезиса и типологии жанра, стилей, преемственности художественно- эстетической традиции. Расскрывается методологическая новизна проблемы историко-литературного, лингвистического исследования жанров, стилей, текстологии казахской филологии на основе работ К.Омиралиева. The article analyzes the characteristics and importance of philological works of the scientist K.Omiraliev in a complex study of the historical ties of kazakh literature and ancient literature in the aspects of the genesis and typology of the genre, style, continuity of artistic and aesthetic traditions. Methodological novelty of the problem of historical and literary, linguistic research genres, styles, textual kazakh philology investigated in this article.